Assessment of Seismic Response of Low-Rise Dual Resistant System comprising of Steel Moment Frame and Zipper Chevron Braced Panels - Ramin Madani (Iranian Society of Structrual Engineering (ISSE), 2020)
In this research, the seismic performance of 5story buildings having dual systems of moment frame and chevron bracings, chevron panels along with zipper columns, inverted chevron panels, inverted chevron panels along with zipper columns is evaluated based on conducting nonlinear time history analyses under an ensemble of 3-component far and near-field records. Behavioral features of resistant skeletons having chevron braced panels are controlled through a near-buckling performance of diagonal limbs under pressure. It has been observed that when intensive earthquakes occur, this type of resistant skeleton reveals a gradual loss in resistant features. The appearance of the effects of the two phenomena of stiffness deterioration and strength degradation would be remarkable. A desirable solution in dealing with this weakness is adding a zipper column to the braced panel. The major criterion in selecting near-field records has been the existence of distinct or compound pulses with long period and large amplitude in the ground velocity time history. It has been noticed that this feature affects the seismic response parameters of the building to a great extent. All structures have been designed with a regular plan and according to seismic provisions in the code 2800 and also the 6th and 10th issues of the Iranian National Building Regulations. The specific outlook of this research lies in assessing the changes in maximum displacement responses, relative velocity, absolute acceleration of the floors, plastic hinge formation mechanism and the axial force of the columns. Results show a moderate superiority in the seismic performance of dual skeleton having zipper elements compared to the same resistant system with a lack of zippers.